Pelatihan Penulisan Karya Ilmiah Bersama Mahasiwa XYZ di Mesir Paper Writing Training with Indonesian Students XYZ di Mesir - Arroisi, Jarman (Khadimul Ummah, 2024)
Requests from Gontor alumni who are studying in Egypt to provide scientific manuscript writing training are very high. Their reasons are very basic because students during their Egyptian studies are not required to write papers or theses as their final assignments. This Community Service (PkM) aims to provide writing training so that Egyptian students who are members of the Pondok Modern Gontor Family Association (IKPM) have provisions for Masters studies. In the preparation of the paper, the author uses a descriptive-analytical method. With the zooming method, this scientific writing training can be carried out with the following results. First, students get a training model for writing scientific papers in general through nine stages. Second, students get guidance on how to write paragraphs and continue with how to quote correctly. Third, students get access to literature references from several national and international journals and various book references from online media. Fourth, students receive training and practice in writing scientific papers with a monitoring and clinic pattern once a week.